Ideal Model of Marital Dispute Mediation in Order to Minimize Divorce Rates - Turatmiyah, Sri (RechtIdee, 2024)
The purpose of marriage is to create an eternal and happy family based on Belief in the One and Only God, as stipulated in Article 1 of Law no. 1 of 1974 concerning Marriage. As a legal relationship, marriage creates legal consequences for the parties, where sometimes the rights and obligations are not carried out by one of the parties. This triggers conflicts that lead to divorce. Indonesian marriage law adheres to the principle of complicating divorce which requires the parties to mediate in resolving divorce disputes. The purpose of this research is to find the ideal model of mediating divorce disputes before being registered with the court as a solution to reduce divorce rates. Normative research methods with library materials as the main legal material. analyzed by descriptive qualitative. The results of this research are divorce mediation which is regulated in Perma No. 1 of 2016 as part of the proceedings in court has not shown significant results. Even though mediation is mandatory, almost in the jurisdiction of the mediation court many failures result in husband and wife ending in divorce. Mediation is based on the meaning of marriage as miitsaqan ghalizhan as the basis for the need for renewal of marriage law in the field of divorce. This mediation model before the dispute is registered with the court on the principle of deliberation to reach a consensus with the aim of maintaining the household. If this ideal mediation fails, then it is registered in court and continued in court.